Uji Aktivitas Pertumbuhan Enterobacter cloacae Selulolitik Aerob Rumen-1 Isolat Asal Limbah Cairan Rumen Sapi Peranakan Ongole (GROWTH ACTIVITY ASSAY OF CELLULOLYTIC BACTERIA ENTEROBACTER CLOACAE SAR 1 (CELLULOLYTIC AEROB RUMEN 1) ISOLATED FROM ONGOLE CRO - Nurhajati, Tri; Soepranianondo, Koesnoto; Lokapirnasari, Widya Paramita (Jurnal Veteriner, 2016)
This study aimedto know the growth activityofcellulolytic bacteria EnterobactercloacaeSAR 1isolatedfrombovinerumen fluidwaste. Isolates that had been cultured were taken as much as 10 mL and thentransferred to100 mL growth medium in Erlenmeyer flask. Culturesuspensions were incubated in a shakerincubator (37°C, 120 rpm). Optical density was measured at ë 600 nm by taking as much as 1 mLsampling with interval of two hours for 24 hours (hour 0; 2; 4; 6; 10; 12; 14; 16; 18; 20; 22; 24). The firstsampling was done at 0thhour and continued until OD values †showed a clear decline. Optical density wasmeasured with a UV-Vis spectrophotometer at wave length ë 600 nm. Growth curve was obtained from theresult of absorbance measurement on the time. Optimum growth production of E.cloacae SAR 1 occurredat the 12thhoursof incubation, optimum temperature of 35°C and optimum pH 6.
Keywords: growth curve; temperature; pH optimum, cellulolytic bacteria